High efficiency heavy metal free QD‐LEDs for next generation displays. Issue 6 (16th April 2019) - Ippen, Christian; Guo, Wenzhuo; Zehnder, Don; Kim, Daekyoung; Manders, Jesse; Barrera, Diego; Newmeyer, Benjamin; Hamilton, Dylan; Wang, Chunming; Hotz, Charlie; Ma, Ruiqing; Bin, Jong‐Kwan; et al.
Abstract: In this paper, we report on our progress on developing heavy metal free (or Cd‐free) QD‐LEDs for all three colors. With improvement in synthesis, we have developed high quantum yield heavy metal free quantum dots (more than 95% for red and green and more than 80% for blue), with peak wavelengths suitable for BT.2020. Building upon these high‐performance quantum dots and through novel device structure design and optimization we have demonstrated high efficiency heavy metal free QD‐LEDs with EQE = 16.9%, 13%, 9% for red, green, and blue, respectively. Specifically, we report a systematic study on the impact of shell thickness to the device efficiency performance. Abstract : We report our progress on developing heavy metal free QD‐LEDs for all three colors. With improvement in synthesis we have developed high quantum yield quantum dots (more than 95% for red and green and more than 80% for blue) with peak wavelengths suitable for BT.2020. We report a systematic study on the impact of shell thickness to the device efficiency performance.